Cerebral metabolism after early decompression craniotomy following controlled cortical impact injury in rats - Zweckberger, Klaus; Hackenberg, Katharina; Jung, Carla Sabine; Hertle, Daniel; Kiening, Karl; Unterberg, Andreas; Sakowitz, Oliver (Neurological research, 2011)
After traumatic brain injury, a cascade of metabolic changes promotes the development of secondary brain damage. In this study, we examined metabolic changes in rats in the acute stage after trauma. Furthermore, we investigated the effect of a very early decompression craniotomy on intracranial pressure (ICP) and on metabolic parameters. For this study, a moderate controlled cortical impact injury (CCII) on rats was performed. The observation time was 180 minutes after trauma. ICP was measured continuously and microdialysate samples were collected every 30 minutes from the peri-contusional region. As representative metabolic parameters, glutamate, lactate, lactate/pyruvate ratio (L/P ratio), and glucose concentrations were measured. Compared to sham-operated animals, a significant, sustained decrease in glucose concentration and increase in L/P ratio occurred immediately after CCII. Additionally, delayed increase in lactate and glutamate concentrations occurred 60 minutes after trauma. After this initial peak, glutamate concentrations declined continuously via the observation time and reached levels comparable to sham-operated animals. In our model, thus we could detect a very early deterioration of glucose utilization and energy supply after trauma that recovered, due to the moderate intensity of the trauma, within 60 minutes without leading to ischemia in the peri-contusional region. Following decompression craniotomy, the increase of intracranial pressure could be reduced significantly. Any significant beneficial effects on metabolic changes, however, could not be proven in this very early stage after moderate CCII.